Giving green: the landscape and motivations of U.S. environmental philanthropy to Brazil - Pinho, Ana Paula Borges (2022)
From the start of the new millennium, the role of philanthropic actors in international development cooperation has been gaining increasing visibility. A growing body of literature on the international activities of foundations has identified several premises connected to these organisations behaviour. For instance, they are thought to take more innovative and riskier approaches than state actors. However, there is limited knowledge about who they give to and how a lack of empirical and systematic analyses to corroborate those premises and demonstrate how foundations actually work. When it comes to environmental philanthropy there is an even bigger gap in knowledge, as much of the extant literature is based on issue areas such as health. The aim of this research is to investigate the trends and patterns in the distribution of international environmental grants by philanthropic organisations, as well as the approaches to giving utilised by these organisations and whether they are motivated by the needs of their grantees. It does so through an in-depth, project-level analysis of the grantmaking practices of three foundations in the United States funding environmental projects in Brazil: Charles Stewart Mott Foundation; Gordon and Betty Moore Foundation; The William and Flora Hewlett Foundation. The objectives are to (i) systematically describe and categorise the foundations studied; (ii) understand the stated priorities and strategies of international foundations supporting environmental issues in Brazil (what foundations say they do); (iii) examine the main practices of these organisations through an in-depth analysis of their grantmaking to Brazilian organisations (what foundations do); (iv) analyse how foundations stated priorities, strategies and practices relate to the assumptions made in the international development cooperation about their behaviour; (v) determine to what degree the needs of grantees motivate foundations giving. The research found that the behaviour of large philanthropic organisations has a lot more in common with the behaviour expected of traditional donors than the literature suggests, including a tendency to risk-aversion. It also found that foundations are acting upon the needs of its grantees, but through a paternalistic altruism that exerts a high level of control over what is done and how it is done. To maintain a relationship with the foundations, recipient organisations need to constantly monitor the strategic and structural changes made by them, which are frequently evolving.